Classification of abdominal vascular anomalies and use of 3D printing to support complex renal transplantation in children. (23rd February 2017) - Chandak, Pankaj; Byrne, Nick; Newton, Victora; Coleman, Andy; Stojanovic, Jelena; Marks, Stephen D; Kessaris, Nicos; Mamode, Nizam
Abstract: Background: Transplantation is the treatment of choice for paediatric renal recipients. However, there are increased challenges in small (<20 kg) children who have complex abnormalities of the abdominal vascular system (aorta and inferior vena cava [IVC]). In this context surgical feasibility and planning is informed by review of medical images. Conventional presentation on a computer screen demands expertise in image interpretation if the spatial associations of complex anatomy are to be fully appreciated. We assessed the feasibility and potential utility of 3D printed models of patient-specific anatomy, as a means to facilitate transplantation. Methods: We describe our management in five paediatric renal recipients with vascular anomalies (median age 7 years [IQR 4·5–13·0], median weight 18 kg [IQR 14·5–29·0]). We assessed the utility of 3D printing as a planning tool in four children with complex abnormalities (one retrospective case, three prospective cases) for whom implantation was uncertain as judged by conventional imaging. Surgically relevant donor and recipient anatomy was segmented from MRI or CT data (Mimics Medical v18.0, Materialise, Leuven, Belgium). The segmentation geometry derived from the extracted anatomical data was then exported in STL file format and physically fabricated with multimaterial, polyjet 3D printing technology (Objet500 Connex1, Objet-Stratasys). We assessed the value of models using questionnaires and geometric validation studies. Findings: Four (80%) of five children survived after one death from sepsis (with a functioning graft). At the latest median follow-up of 19 months (IQR 10·5–83·0) renal allograft survival was 100% (death censored) with a median estimated glomerular filtration rate of 55 mL/min per 1·73 m 2 (IQR 45–66). We have previously classified these vascular anomolies on the basis of aortic and IVC patency (I=aorta patent, II=infrarenal segment occluded, III=suprarenal segment occluded, IV=all aorta occluded) and similarly for IVC patency (A–D). By independent questionnaire, all prospective 3D printed models were considered useful for preoperative planning, and thereby facilitated transplantation. In our retrospective proof of concept, Bland–Altman analysis found that the mean difference in vascular diameter between the printed model and segmentation geometry was −0·1 mm (95% CI −0·7 to 0·5), which was insignificant when compared with the measurement uncertainty (±0·4 mm) and the limits of surgical precision. All models showed geometrical consistency with preprinting designs and intraoperative anatomical correlation within surgical acceptance for crucial decision making. Interpretation: Vascular anomalies do not necessarily preclude transplantation, and a classification system could guide management. Our feasibility study of patient-specific 3D printing suggests that cases classified as sufficiently complex can benefit from this technology. Patient-specific models provide the surgical team with the full, 3D, accessible, haptic, and spatial appreciation of anatomy that is crucial in surgical decision making and planning. This technology can inform the selection of suitable anastamosis sites in the presence of anomalies and the best surgical approach for implantation of an adult-sized kidney into a small child. Funding: None.